INTERVENSI TERAPI BEKAM DAN SENTUHAN QUANTUM MENURUNKAN KADAR GULA DARAH PENDERITA DIABETES MELITUS (DM) - Irmayani Irmayani; Antok Nurwidi Antara; Yuli Ernawati (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Introduction: In many nations, the number of diabetics (DM) is steadily increasing. Diabetes mellitus treatment begins with implementing a healthy lifestyle (medical nutrition therapy and physical activity), as well as pharmaceutical intervention using anti-hyperglycemic medications orally or by injection. Wet cupping therapy is complementary non- pharmacological therapy that is often used by people with diabetes mellitus and has been proven to reduce blood sugar level. Cupping is a method of drawing blood from the peripheral skin surface by suctioning or cupping. Small incisions are then made on the outer skin, and suction is applied again to draw out blood. This is believed to remove toxins from the body, which can decrease blood sugar levels. Methods: This research design uses pre-experimentation with a one-group pre-test - post-test research plan. The number of samples used was 15 respondents, while data collection was carried out using the Non-probability Sampling technique with the Total Sampling method. This research was held at Rumah Sehat Insani Kalasan Clinic with 1 time of intervention of quantum healing touch and wet cupping therapy. Results: There was an effect of wet cupping therapy and quantum touch therapy on reducing blood sugar levels in diabetes mellitus sufferers after intervention, a significant value of p=0.001 (p<0.05) was obtained. Conclusion: Cupping complementary therapy is one of the therapies used by diabetes mellitus (DM) sufferers to lower their blood sugar levels. Nurses in implementing nursing care can add this therapy. However, it needs to be further developed on how many times cupping therapy should be carried out so that blood sugar levels can be controlled. Keywords: Wet cupping, diabetes mellitus, blood sugar, quantum touch therapy